2009
DOI: 10.1111/j.1442-2042.2009.02386.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transperineal 14‐core systematic prostate biopsy in diabetic men

Abstract: Objectives: To examine whether the transrectal ultrasound-guided transperineal 14-core prostate biopsy can be carried out safely in diabetic men and to determine adequate antimicrobial prophylaxis protocol in this setting. Methods: The present study included 539 men, 135 with concurrent diabetes mellitus (DM) and 404 without DM, who underwent transperineal extended 14-core biopsy due to elevated prostate-specific antigen Ն2.5 ng/mL and/or abnormal digital rectal examination. Any complication requiring prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“… (51%) and Vyas et al. (54%) (Table ) . The only other TPB series published in Australia was by Symons et al.…”
Section: Discussionmentioning
confidence: 90%
“… (51%) and Vyas et al. (54%) (Table ) . The only other TPB series published in Australia was by Symons et al.…”
Section: Discussionmentioning
confidence: 90%
“…They concluded that transperineal biopsy can be carried out without major infectious complications in diabetic men. 19 Finally, it important to monitor these patients and inform them that they should contact the referral department at the beginning of the onset of symptoms. The present study showed full recovery with no urosepsis when the patients were admitted quickly and treated appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Each biopsy core was individually labelled so that the location of cancer‐positive cores could be analysed . Biopsy‐related complications were prospectively evaluated, as reported elsewhere, and those that required hospitalisation were assigned to the major category . Cancers were classified as biopsy‐based significant cancers when biopsy Gleason score (GS) was 4 + 3 or greater and/or percentage of positive cores was >50% and/or maximum cancer occupation was >50% and/or PSA density was >0.15 (definition 1), and when biopsy GS was 3 + 4 or greater and/or percentage of positive cores was >50% and/or maximum cancer occupation was >50% and/or PSA density was >0.15 (definition 2).…”
Section: Methodsmentioning
confidence: 99%